Adaptation of Hevea brasiliensis clones in three widely different cold prone areas of northeastern India - Das G; Chaudhuri D; Mondal G C; Reju M J; Singh R P; Thapliyal A P (Indian Journal of Plant Physiology, 2013)
Growth and yield of clones cultivated in three climatologically widely different areas viz. Ganolgre (Tura, Meghalaya), Nagrakatta (Jalpaiguri, West Bengal) and Sarutari (Kamrup, Assam) were compared to understand the behavioral difference of the clones under the native climate. Clone trials were initiated at the three locations with 14 clones along with a check clone. The growth period over years was separated as non-winter (NW-April to September) and winter (W-October to March) periods. A clear indication of adverse effect of low winter temperature on girth increment was observed. Girth of Hevea clones at 20th year of growth with high biomass was found to be better in the climatic condition of Ganolgre than Nagrakata followed by Sarutari. It seems that the optimum rainfall and marginally suitable slope along with proper range of low winter temperature favoured better growth in Ganolgre compared to that in Nagrakatta though altitude of Ganolgre was more than Nagrakatta. Yield of all the clones were at par with or lower than the check clone. Yield in Nagrakata was the best among the three locations followed by Sarutari; and it was lowest in Ganolgre. The study explored the scope of cultivating Hevea brasiliensis in severe cold prone areas, which in future may be come partially cold prone areas due to gradual but steady change in climate.
Source Year: 2013
Keywords: Adaptation; Agroclimate; Biomass; Growth rate; Yield